2019
DOI: 10.1111/ecc.13048
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty and sense‐of‐self as targets for intervention for cancer‐related fatigue

Abstract: Cancer‐related fatigue (CRF) can be a devastating consequence of cancer and cancer treatments, negatively impacting 50%–90% of cancer patients regardless of age, sex or diagnosis. Limited evidence and research exist to inform effective patient‐centred interventions. To target symptom management, there must first be a broader understanding of the symptoms and the lived experience of the persons experiencing CRF and those caring for them, from a supportive as well as a healthcare perspective. This study set out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
(30 reference statements)
0
9
0
Order By: Relevance
“…The CRF affects 50% to 90% of cancer patients regardless of age, sex or diagnosis [ 85 ], persisting after the end of treatment [ 86 , 87 ] and presenting emotional, physical, cognitive, functional consequences, in addition to causing uncertainty and impact the sense-of-self [ 88 ]. In the present study, CRF was associated with practically all health outcomes investigated, being relevant result for clinical practice and reinforces the need for more studies aimed at the development of effective interventions to control this adverse effect whit high potential for better the HRQL and associated aspects.…”
Section: Discussionmentioning
confidence: 99%
“…The CRF affects 50% to 90% of cancer patients regardless of age, sex or diagnosis [ 85 ], persisting after the end of treatment [ 86 , 87 ] and presenting emotional, physical, cognitive, functional consequences, in addition to causing uncertainty and impact the sense-of-self [ 88 ]. In the present study, CRF was associated with practically all health outcomes investigated, being relevant result for clinical practice and reinforces the need for more studies aimed at the development of effective interventions to control this adverse effect whit high potential for better the HRQL and associated aspects.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24] The resolution of fatigue may, therefore, not be solely dependent on stopping treatment, but may also involve other factors such as patient lifestyle or mental health status. [25][26][27] The fast resolution of the AEs (1-3 days except for fatigue) for axitinib monotherapy is most likely due to its short half-life. After a single 5-mg dose, the half-life of axitinib is 2.5 to 6.1 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the physical, emotional and functional consequences of CCRF, people also described how this fatigue impacted the sense of self and created feelings of uncertainty related to the onset, duration, impact and management of the fatigue. Based on these findings, the authors concluded that interventions addressing uncertainty and altered sense of self may be helpful to them (Dolgoy et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This method could help unravel if the interrelated problems a patient suffers from belong to one phenomenon or differentiate into distinctly different phenomena with different etiologies, and investigate the preferred word choice to determine possible targets for treatment (Laidsaar-Powell et al, 2019). For example, Dolgoy et al (2019) identified new intervention targets by studying how people affected by cancer spontaneously described the nature and impact of fatigue. Besides the physical, emotional and functional consequences of CCRF, people also described how this fatigue impacted the sense of self and created feelings of uncertainty related to the onset, duration, impact and management of the fatigue.…”
Section: Introductionmentioning
confidence: 99%